2020
DOI: 10.3390/ani10071206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral Supplementation on the Macromineral Concentration in Blood in Pre- and Postpartum Blackbelly Sheep

Abstract: The objective of this study was to determine the effect of mineral supplementation on the serum concentration of calcium, phosphorus, and magnesium in pre- and postpartum Blackbelly sheep throughout three successive lambing periods under free grazing conditions in the Ecuadorian Amazon Region. The field work was carried out between January 2015 and February 2018 using 20 Blackbelly sheep belonging to the Centre for Research, Postgraduate Studies and Conservation of Amazon Biodiversity, Ecuador. The flock was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To uniform this study, the serum samples were used to measure both the concentration of the mineral elements and the biochemical parameters. It was found out that the normal serum Ca concentration in junior sheep ranged from 70 mg/L to 80 mg/L ( 3 ). In this research, the mean value of the initial concentration of Ca reached 51.61 mg/L, indicating that the Ca deficiency found in Mongolian Wu Ranke sheep resulted from their long-term pattern of grazing in the grassland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To uniform this study, the serum samples were used to measure both the concentration of the mineral elements and the biochemical parameters. It was found out that the normal serum Ca concentration in junior sheep ranged from 70 mg/L to 80 mg/L ( 3 ). In this research, the mean value of the initial concentration of Ca reached 51.61 mg/L, indicating that the Ca deficiency found in Mongolian Wu Ranke sheep resulted from their long-term pattern of grazing in the grassland.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the intake of various nutrients by livestock is closely related to the types and amounts of nutrients provided by the grassland in OPEN ACCESS EDITED BY Fazul Nabi, Lasbela University of Agriculture, Water and Marine Sciences, Pakistan the pasture. However, some research has revealed that pasture is incapable to provide all the nutrients needed for the normal growth and metabolic processes of livestock, especially minerals (3,4). Various mineral elements are required for the metabolism of livestock through various physiological and biochemical processes.…”
Section: Introductionmentioning
confidence: 99%